The Effect of the STAD Type Learning Model on Student Learning Outcomes in the Material of Temperature and Heat at SD Negeri 53 Banda Aceh - azhari, kamila fitri; Ahadin, Ahadin; Husin, M. (Elementary Education Research, 2023)
This study intends to investigate the impact of using the cooperative learning model type STAD assisted by interactive power points on student learning outcomes at SD Negeri 53 Kota Banda Aceh in the material temperature and heat. True experiment is the method applied in this study with a pre-test and post-test control group design and a quantitative approach. The sample consisted of 24 students of class V who were randomly selected. Data was collected through a test of 20 multiple choice questions after 3 meetings. Data analysis was performed using a t-test with a significance level of 0.05. Based on the results of the study, it showed an increase in student learning outcomes after applying the STAD type of cooperative learning model. In addition, students are more active in learning using this model compared to conventional learning. The use of the STAD type of cooperative learning model with interactive power point has proven to have an effect on student learning outcomes in the matter of temperature and heat.